Reorientation of Spiritual Educational Thought in Islam And its Correlation to Mental Health - Hidayat, Yayat; Hafizah, Noor; Sumedi, Sumedi; Chasani, Muchamad Toif (Jurnal Sustainable, 2023)
Epistemology in Islam and its relation to the content and process of Muslim education is the subject of study in this article. Perceptions related to Islamic revivalism that spread in several regions of the world demand an integrated education system based on Islam. Spiritual education provides religious and academic currents with various implications for forming mental health. This article examines the reorientation of spiritual education thought in Islam. This study is interesting to do considering the thought of spiritual education from the point of view of the Al-Quran and Sunnah does not appear as a disconnected educational thought but a living and dynamic thought construction. This study is a literature study with a qualitative approach, while the theory used was the theory of Islamic education initiated by educational thinkers. Hence, spiritual education’s ultimate goal is identical to creating servants in realizing servitude, giving rise to mental health as a parameter of happiness in life.